Students Ability to Analyze Homophones in the Animation Video 端午节 Duānwǔ jié (Dragon Boat Festival) on the YouTube Channel 三淼儿童官方频道 Sān miǎo értóng guānfāng píndào - Andini, Batari; Rahmawati, Vina Dwi; Ningsih, Tri Wahyu Retno (Bambuti, 2025)
Abstract. Homophones are the similarities in sound that occur in a word regardless of its spelling. In Mandarin, homophones are the similarity of sounds and tones in different Han characters and have different meanings. The purpose of this study was to determine the ability of Grade 2 students on homophonic words in the 端午节Duānwǔ jié (Dragon Boat Festival) Animation Video on the 三淼儿童官方频道Sān miǎo értóng guānfāng píndào Youtube Channel. The research method used is qualitative which is described descriptively. There are 10 test questions that are used to determine the ability of grade 2 students to homophonic words. The result of this study is that the majority of students have understood homophonic vocabulary. Keywords: Homophones, 端午节Duānwǔ jié (Dragon Boat Festival) Animation Video on the 三淼儿童官方频道Sān miǎo értóng guānfāng píndào Youtube Channel. Abstract (in Bahasa). Homofon adalah kesamaan bunyi yang terjadi pada sebuah kata tanpa memperhatikan ejaannya. Dalam bahasa Mandarin, homofon merupakan kesamaan bunyi dan ton pada suatu karakter Han yang berbeda dan makna yang berbeda pula. Tujuan dari penelitian ini adalah untuk mengetahui kemampuan Mahasiswa Tingkat 2 dalam menganalisis Homofon Pada Video Animasi 端午节Duānwǔ jié (Festival Perahu Naga) Di Kanal Youtube 三淼儿童官方频道Sān miǎo értóng guānfāng píndào. Metode penelitian yang digunakan adalah kualitatif yang diuraikan secara deskriptif. Terdapat 10 soal tes yang digunakan untuk mengetahui kemampuan mahasiswa tingkat 2 dalam menganalisis kata berhomofoni. Hasil dari penelitian ini adalah mayoritas mahasiswa telah memahami kosa kata yang berhomofoni. Kata kunci: homofon, Video Animasi 端午节Duānwǔ jié (Festival Perahu Naga) Di Kanal Youtube 三淼儿童官方频道Sān miǎo értóng guānfāng píndào.